Technical and Economic Feasibility Study of Coconut Shell Charcoal Production as Precursor to Activated Carbon in East Coast Malaysia - Wan Muhammad Noor Sarbani Mat Daud; Shariman Mustafa; Syed Radzi Rahmadulla; Saiful Anwar bin Che Ghani; Anwaruddin Hisyam (International Journal of Supply Chain Management, 2017)
The most common precursors used for the preparation of activated carbons are organic materials that are rich in carbon. The abundance and availability of coconut shells make them excellent sources of raw materials for activated carbon production. A survey has been conducted to identify locations for the supply of coconut shells. The survey has been conducted around a coastal village of Beserah, Kuantan. The cost calculation for two methods was considered, which is to buy from coconut supplier or to do self-collection at the coconut milk entrepreneurs location. Two carbonization methods were used in this study which is traditional drum method and Top-Lit up-Draft (TLUD) drum method. The results from the both methods were observed. The coconut shell charcoals produced were sent to activated carbon manufacturer for evaluation. The coconut shell charcoals from the different methods were priced differently. This is mainly due to different quality of the charcoals. A calculation of possible cost and sales from a small production plant was simulated to know whether a profitable production plant could be set-up. The most common precursors used for the preparation of activated carbons are organic materials that are rich in carbon. The abundance and availability of coconut shells make them excellent sources of raw materials for activated carbon production. A survey has been conducted to identify locations for the supply of coconut shells. The survey has been conducted around a coastal village of Beserah, Kuantan. The cost calculation for two methods was considered, which is to buy from coconut supplier or to do self-collection at the coconut milk entrepreneurs location. Two carbonization methods were used in this study which is traditional drum method and Top-Lit up-Draft (TLUD) drum method. The results from the both methods were observed. The coconut shell charcoals produced were sent to activated carbon manufacturer for evaluation. The coconut shell charcoals from the different methods were priced differently. This is mainly due to different quality of the charcoals. A calculation of possible cost and sales from a small production plant was simulated to know whether a profitable production plant could be set-up.